A low-temperature, photoinduced thiol–ene click reaction: a mild and efficient method for the synthesis of sugar-modified nucleosides. Issue 43 (31st October 2017) - Bege, Miklós; Bereczki, Ilona; Herczeg, Mihály; Kicsák, Máté; Eszenyi, Dániel; Herczegh, Pál; Borbás, Anikó
Abstract : While studying the radical mediated hydrothiolation of nucleoside enofuranosides, an unusual temperature effect was observed by the exploitation of which various thio-substituted nucleoside analogues were produced. Abstract : Sugar-modified nucleosides are prime synthetic targets in anticancer and antiviral drug development. Radical mediated thiol–ene coupling was applied for the first time on nucleoside enofuranoside derivatives to produce a broad range of thio-substitutedd - ribo, - arabino, - xylo andl - lyxo configured pyrimidine nucleosides. In contrast to the analogous reactions of simple sugar exomethylenes, surprisingly, hydrothiolation of nucleoside alkenes under the standard conditions of various initiation methods showed low to moderate yields and very low stereoselectivity. Optimizing the reaction conditions, we have found that cooling the reaction mixture has a significant beneficial effect on both the conversion and the stereoselectivity, and UV-light initiated hydrothiolation of C 2′-, C 3′- and C 4′-exomethylene derivatives of nucleosides at −80 °C proceeded in good to high yields, and, in most cases, in excellent diastereoselectivity. Beyond the temperature, the solvent, the protecting groups on nucleosides and, in some cases, the configuration of the thiols also affected the stereochemical outcome of the additions. The anomalousl - lyxo diastereoselectivity observed upon the addition of 1-thio-β-d -gluco- and galactopyranose derivatives onto C 4′, 5′-unsaturated uridines is attributed to steric mismatch between thed - ribo C 4′-radical intermediates and the β-configured 1-thiosugars.